Surgery of the Palatomaxillary Structure - Jategaonkar, Ameya A.; Kaul, Vivian F.; Lee, Eric; Genden, Eric M. (Seminars in Plastic Surgery, 2020)
The palatomaxillary structure plays critical roles in both form and function of the midface. Surgical defects of the palate and maxilla can be associated with significant morbidity and deformity. Various defect classification systems have been used to assist in reconstruction and rehabilitation. Reconstructive options include prosthetic rehabilitation, local flaps, and free tissue transfer. Here, we review the functional and surgical anatomy of the palatomaxillary complex, defect classification systems, and provide an overview of reconstructive options.
Keywords: head and neck surgery; maxillectomy; palatectomy; palate/palatal surgery; midface surgery